An α-NaFeO2@N-MXene composite material, its preparation method and application

CN116936757BActive Publication Date: 2026-09-15SHENZHEN DYNANONIC CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310167307.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-27
Publication Date
2026-09-15
Estimated Expiration
2043-02-27

AI Technical Summary

Technical Problem

从现有的研究结果来看,无论多种金属元素的混合还是复合相的构建,对α-NaFeO2电化学性能的改善效果不佳,α-NaFeO2依然存在导电性和循环稳定性不足的问题

Benefits of technology

[0048] (1) In the preparation method provided by the present invention, N-Mxene is combined with a specific process to form a stable two-dimensional ion conduction channel in the obtained α-NaFeO2@N-MXene composite material, which has excellent electrical conductivity and electron transport conduction performance, good rate performance, and can effectively suppress the collapse of the layered structure of α-NaFeO2 electrode material during the charging and discharging process, especially in the early stage of charging and discharging, reduce the rate of capacity decay, improve the first coulombic efficiency and cycle performance, and has excellent comprehensive electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116936757B_ABST
    Figure CN116936757B_ABST
Patent Text Reader

Abstract

The application provides an alpha-NaFeO2@N-MXene composite material and a preparation method and application thereof, and the preparation method comprises the following steps: mixing a sodium source and an iron source, and then performing first calcination to obtain alpha-NaFeO2; mixing the alpha-NaFeO2 and N-Mxene, and then performing second calcination to obtain the alpha-NaFeO2@N-MXene composite material. The alpha-NaFeO2@N-MXene composite material obtained by combining N-Mxene with a specific process has a stable two-dimensional ion conduction channel, excellent conductivity and electron transmission and conduction performance, good rate performance, and can effectively inhibit the collapse of a layered structure of an alpha-NaFeO2 electrode material in a charging and discharging process, especially in an early charging and discharging stage, reduce the rate of capacity attenuation, improve the first coulombic efficiency and cycle performance, and has excellent comprehensive electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion battery materials technology, specifically relating to an α-NaFeO2@N-MXene composite material, its preparation method, and its application. Background Technology

[0002] Due to the abundance and wide availability of sodium on Earth, sodium-ion batteries are considered one of the sustainable energy storage technologies that can replace lithium-ion batteries for large-scale energy storage. The cathode material, as a crucial component of sodium-ion batteries, determines their electrochemical performance. Layered sodium-containing transition metal oxides possess advantages such as simple structure, ease of synthesis, high theoretical specific capacity, operating voltage, and cycle stability, making them highly promising cathode materials for commercial applications in sodium-ion batteries. Among layered sodium-containing transition metal oxides, α-NaFeO2 is considered a cathode material with significant application potential due to its abundant raw materials, non-toxicity, and low cost.

[0003] Because lithium ions and ferric ions have similar diameters, they easily mix and merge. Therefore, layered LiFeO2 is electrochemically inert and difficult to apply. + Its diameter is 1.02 angstroms, significantly larger than that of Fe. 3+ With a diameter of 0.645 Å, there is no mixing phenomenon, which is conducive to the separation of the sodium layer and the transition metal layer. Therefore, α-NaFeO2 has high structural stability and electrochemical activity. The O3 phase layered oxide is used as the positive electrode material, utilizing Fe 3+ / Fe 4+ Redox reactions can achieve good capacity properties. However, after charging, about 20% of the tetravalent iron in the α-NaFeO2 electrode material spontaneously reverts to the trivalent iron state, causing the layered structure to collapse and thus leading to a deterioration in electrochemical performance.

[0004] To improve the electrochemical performance of layered oxide cathode materials such as α-NaFeO2, researchers have attempted to provide solutions from aspects such as composition design and composite phase construction. From the perspective of composition design, methods such as mixing different types of transition metal elements or introducing electrochemically inert elements (e.g., Li, Mg, Al) into the structure can mitigate structural changes and improve electrochemical performance, especially cycle stability. For example, CN113716622A discloses an iron-based layered oxide cathode active material that uses Fe as the base element, partially replacing Fe with metal element M1 (at least one of Ni, Mn, Cu, Co), and combining the effects of metal element M2 (at least one of Mg, Al, Ti, Zr) and Re doping to better maintain the structural stability of the electrode material during operation. From the perspective of composite phase construction, compared to single-phase materials, composite phase structures can simultaneously possess the characteristics of multiple single phases, which helps improve ionic conductivity or can influence the irreversible structural transformation of the primary phase through phase interfaces, thereby improving the electrochemical performance of the material. For example, CN112262109A discloses an O3 / P2 mixed-phase sodium-doped layered oxide material, which comprises a mixture of a first phase with an O3-type structure and a second phase with a P2-type structure. By changing the process conditions used to prepare this target sodium-doped layered oxide material, especially by changing the heating and sintering temperature and / or time, a series of O3 / P2 phases with different proportions can be obtained for a single target sodium-doped layered oxide material composition. Existing research results show that neither mixing multiple metal elements nor constructing composite phases has a significant effect on improving the electrochemical performance of α-NaFeO2; α-NaFeO2 still suffers from insufficient conductivity and cycle stability. Therefore, improving the electrochemical performance of α-NaFeO2 cathode materials is an urgent problem to be solved in this field. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide an α-NaFeO2@N-MXene composite material, its preparation method, and its applications. The α-NaFeO2@N-MXene composite material obtained through a specific preparation method exhibits excellent electron transport and conductivity properties, and its electrochemical properties, such as rate performance, cycling performance, and initial coulombic efficiency, are effectively improved.

[0006] To achieve this objective, the present invention adopts the following technical solution:

[0007] In a first aspect, the present invention provides a method for preparing α-NaFeO2@N-MXene composite material, the preparation method comprising the following steps:

[0008] The sodium source and the iron source were mixed and calcined once to obtain α-NaFeO2;

[0009] The α-NaFeO2 and N-MXene were mixed and then calcined twice to obtain the α-NaFeO2@N-MXene composite material.

[0010] The preparation method provided by this invention first involves preparing α-NaFeO2 via solid-state synthesis, then mixing it with N-Mxene (nitrogen-doped MXene, i.e., nitrogen-doped two-dimensional inorganic material) and subjecting it to secondary calcination. This process forms a conductive network coating structure composed of two-dimensional N-Mxene on the outside of α-NaFeO2, resulting in the α-NaFeO2@N-MXene composite material. This preparation method is simple, has a high yield, and is suitable for industrial mass production. In the α-NaFeO2@N-MXene composite material, N-Mxene and α-NaFeO2 work together to form a stable two-dimensional ion-conducting channel, exhibiting excellent electrical conductivity and electron transport performance. Furthermore, it effectively suppresses the collapse of the layered structure of the α-NaFeO2 electrode material during battery charging and discharging, especially in the early stages of charging and discharging, thereby reducing the capacity decay rate and improving the initial coulombic efficiency and cycle performance.

[0011] Preferably, the method for mixing the sodium source and the iron source is ball milling, and more preferably dry ball milling.

[0012] Preferably, the ball milling mixing time is 0.5-12h, for example, it can be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h or 11h, as well as specific point values ​​between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific point values ​​included in the range.

[0013] Preferably, the ball milling speed is 200-500 r / min, for example, it can be 220 r / min, 250 r / min, 280 r / min, 300 r / min, 320 r / min, 350 r / min, 380 r / min, 400 r / min, 420 r / min, 450 r / min or 480 r / min, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0014] Preferably, the molar ratio of sodium in the sodium source to iron in the iron source is 1:(0.1-10), for example, it can be 1:0.2, 1:0.5, 1:0.8, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8 or 1:9, etc.

[0015] Preferably, the temperature of the first calcination is 300-1000℃, for example, it can be 350℃, 400℃, 450℃, 500℃, 550℃, 600℃, 650℃, 700℃, 750℃, 800℃, 850℃, 900℃ or 950℃, as well as specific values ​​between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0016] Preferably, the calcination time is 3-24 hours, for example, it can be 4 hours, 6 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours or 22 hours, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0017] Preferably, the atmosphere for the primary calcination includes any one or a combination of at least two of air, oxygen, argon, and nitrogen.

[0018] Preferably, the apparatus for primary calcination includes a tubular furnace.

[0019] Preferably, the calcination process further includes a purification step.

[0020] Preferably, the purification method is washing and drying.

[0021] Preferably, the washing agent is an organic solvent.

[0022] Preferably, the organic solvent includes alcohol solvents and / or ester solvents, and more preferably includes any one or a combination of two or more of ethanol (anhydrous ethanol), ethylene glycol, dimethyl carbonate, methanol, propanol, and butanol.

[0023] The propanol includes n-propanol and / or isopropanol, and the butanol includes any one or a combination of at least two of n-butanol, isobutanol, and tert-butanol.

[0024] Preferably, the drying temperature is 50-120℃, for example, it can be 55℃, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, 100℃, 105℃, 110℃ or 115℃, as well as specific values ​​between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0025] Preferably, the purity of the α-NaFeO2 is 98% or higher, for example, the purity can be 98.2%, 98.5%, 98.8%, 99%, 99.2%, 99.5%, 99.8% or 100%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0026] Preferably, the mass ratio of α-NaFeO2 to N-Mxene is 1:(1-10), for example, it can be 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8 or 1:9, etc.

[0027] As a preferred embodiment of the present invention, the mass ratio of α-NaFeO2 to N-Mxene is 1:(1-10). The reasonable combination and synergistic effect of the two components enables N-Mxene to effectively coat and modify α-NaFeO2, resulting in an α-NaFeO2@N-MXene composite material with excellent conductivity, rate performance, initial coulombic efficiency, and cycle performance. Excessive use of N-Mxene will degrade the processing performance of the electrode, hindering capacity utilization; insufficient use of N-Mxene will fail to effectively improve the conductivity of the composite material and will also make it difficult to suppress the collapse of the layered structure of the α-NaFeO2 electrode material during charge and discharge, resulting in no significant improvement in electrochemical performance.

[0028] Preferably, the method for mixing α-NaFeO2 and N-Mxene is ball milling, and more preferably dry ball milling.

[0029] Preferably, the ball milling mixing time is 5-10 hours, for example, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours or 9.5 hours, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0030] Preferably, the ball milling speed is 200-500 r / min, for example, it can be 220 r / min, 250 r / min, 280 r / min, 300 r / min, 320 r / min, 350 r / min, 380 r / min, 400 r / min, 420 r / min, 450 r / min or 480 r / min, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0031] As a preferred technical solution of the present invention, the two mixing methods in the preparation method are dry ball milling mixing, which allows the solid powders to fully contact and mix. The process is simple and low in cost. Since α-NaFeO2 is easily hydrolyzed when it comes into contact with water and is sensitive to moisture, the dry ball milling mixing does not require the use of expensive high-purity solvents or additional drying steps, making it more suitable for industrial production.

[0032] Preferably, the temperature of the secondary calcination is 200-500℃, for example, it can be 220℃, 250℃, 280℃, 300℃, 320℃, 350℃, 380℃, 400℃, 420℃, 450℃ or 480℃, as well as specific values ​​between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0033] Preferably, the secondary calcination time is 2-10 hours, for example, it can be 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours or 9 hours, as well as specific values ​​between the above-mentioned values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0034] Preferably, the atmosphere for the secondary calcination is an inert atmosphere, and more preferably argon and / or nitrogen.

[0035] Preferably, the apparatus for secondary calcination includes a tubular furnace.

[0036] Preferably, the sodium source includes any one or a combination of at least two of sodium oxide, sodium hydroxide, and sodium salt; more preferably, it includes any one or a combination of at least two of sodium carbonate, sodium nitrate, sodium acetate, sodium oxalate, sodium hydroxide, sodium sulfate, and sodium peroxide.

[0037] Preferably, the iron source includes any one or a combination of at least two of ferric salts (trivalent ferric salts), ferrous salts (divalent ferric salts), and iron oxides; more preferably, it includes any one or a combination of at least two of ferric nitrate, ferric oxide, ferrous oxalate, ferric oxide, ferrous sulfate, and ferric chloride.

[0038] Preferably, the preparation method specifically includes the following steps:

[0039] (1) After dry ball milling and mixing sodium source and iron source, calcination is carried out at 300-1000℃ for 3-24h to obtain crude product;

[0040] (2) The crude product is washed with an organic solvent and dried to obtain α-NaFeO2, and the purity of the α-NaFeO2 is above 98%.

[0041] (3) The α-NaFeO2 and N-Mxene are mixed by dry ball milling at a mass ratio of 1:(1-10), and then calcined at 200-500℃ in an inert atmosphere for 2-10h to obtain the α-NaFeO2@N-MXene composite material.

[0042] In a second aspect, the present invention provides an α-NaFeO2@N-MXene composite material, which is prepared by the preparation method described in the first aspect.

[0043] Preferably, the initial coulombic efficiency of the α-NaFeO2@N-MXene composite material is ≥87.5%, and can be 87.5-88.3%.

[0044] On the other hand, the present invention provides an application of the α-NaFeO2@N-MXene composite material in the cathode material of sodium-ion batteries.

[0045] Preferably, the α-NaFeO2@N-MXene composite material is used as a positive electrode material in sodium-ion batteries, and its cycle capacity retention rate is >92%, which can be 92.3-93.1%.

[0046] Thirdly, the present invention provides a sodium-ion battery comprising the α-NaFeO2@N-MXene composite material as described in the second aspect.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] (1) In the preparation method provided by the present invention, N-Mxene is combined with a specific process to form a stable two-dimensional ion conduction channel in the obtained α-NaFeO2@N-MXene composite material, which has excellent electrical conductivity and electron transport conduction performance, good rate performance, and can effectively suppress the collapse of the layered structure of α-NaFeO2 electrode material during the charging and discharging process, especially in the early stage of charging and discharging, reduce the rate of capacity decay, improve the first coulombic efficiency and cycle performance, and has excellent comprehensive electrochemical performance.

[0049] (2) The preparation method provided by the present invention has a simple process route, high yield, and is suitable for industrial mass production. Attached Figure Description

[0050] Figure 1 The image shows a comparison of the XRD patterns of the crude product obtained in the preparation method provided in Example 1 and α-NaFeO2. Detailed Implementation

[0051] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0052] The terms “comprising,” “including,” “having,” “containing,” or any other variations thereof, as used herein, are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not limited to those elements and may also include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.

[0053] "Optional" or "any one" means that the matter or event described thereafter may or may not occur, and the description includes both the possibility that the event will occur and the possibility that the event will not occur.

[0054] The indefinite articles “a” and “an” preceding an element or component of this invention do not impose any limitation on the quantity (i.e., number of times) of the element or component. Therefore, “an” or “a” should be interpreted as including one or at least one, and the singular form of an element or component also includes the plural form, unless the quantity clearly refers only to the singular form.

[0055] The terms "one embodiment," "some embodiments," "exemplary," "specific example," or "some examples," etc., used in this invention refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the invention. In this document, the illustrative expressions of the above terms are not necessarily directed at the same embodiment or example.

[0056] Furthermore, the technical features involved in the various embodiments of the present invention can be combined with each other as long as they do not conflict with each other.

[0057] In the following specific embodiments of the present invention, all raw materials used are commercially available products; among them, N-MXene was purchased from Xi'an Qiyue Biotechnology Co., Ltd., and MXene was purchased from Nanjing Xianfeng Nanomaterials Technology Co., Ltd.

[0058] Example 1

[0059] An α-NaFeO2@N-MXene composite material and its preparation method are described below:

[0060] (1) 4.24g of NaNO3 and 3.2g of Fe2O3 were placed in an agate mortar and mixed evenly, then transferred to a ball mill jar. Ball milling beads of different sizes were added to the jar, and the mixture was ball milled at 350r / min for 6h. The resulting brown solid powder A was obtained.

[0061] The brown solid powder A was placed in a corundum boat, and the corundum boat was transferred to a corundum tube furnace. Under N2 atmosphere, it was calcined at 600°C for 5 hours and then cooled to room temperature with the furnace to obtain α-NaFeO2 containing impurity phases, which was denoted as orange powder B (crude product).

[0062] (2) The orange powder B obtained in step (1) was washed and purified with anhydrous ethanol. Then the washed powder was dried in a vacuum drying oven at 100°C to obtain high-purity α-NaFeO2, which was denoted as orange-red powder C.

[0063] (3) Weigh 1.5g of the orange-red powder C obtained in step (2) and 3.5g of N-MXene into an agate mortar and mix evenly. Then transfer it to a ball milling jar, add ball milling beads of different sizes into the jar, and ball mill at 400r / min for 12h. After that, take it out to obtain solid powder D.

[0064] The solid powder D was placed in a quartz boat, and the quartz boat containing the sample was transferred to a tube furnace. Under an argon atmosphere, it was calcined at 500°C for 2.5 hours. After the tube furnace was cooled to room temperature, the sample was removed, which is the α-NaFeO2@N-MXene composite material.

[0065] The crystal structure of the α-NaFeO2 material obtained in this embodiment was tested using an X-ray diffractometer (XRD, Bruker D8 Advance). The XRD comparison diagrams of the crude product (orange powder B) obtained in step (1) and the high-purity α-NaFeO2 obtained in step (2) are shown below. Figure 1 As shown, combined with Figure 1 It can be seen that after cleaning and purification with organic solvents, the α-NaFeO2 has high purity and no impurity peaks from NaNO2.

[0066] Example 2

[0067] An α-NaFeO2@N-MXene composite material and its preparation method are described below:

[0068] (1) 4.293g of Na2CO3 and 5.79g of Fe3O4 were placed in an agate mortar and mixed evenly, then transferred to a ball milling jar. Ball milling beads of different sizes were added to the jar and the mixture was ball milled at 300r / min for 6 hours. The black solid powder A was then obtained.

[0069] The black solid powder A was poured into an alumina boat, and the alumina boat was transferred to an alumina tube furnace. The alumina boat was calcined at 700°C for 10 hours in an air atmosphere. After cooling to room temperature with the furnace, α-NaFeO2 containing impurity phases was obtained, which was denoted as orange powder B (crude product).

[0070] (2) The orange powder B obtained in step (1) was washed and purified with anhydrous ethanol. Then the washed powder was dried in a vacuum drying oven at 120°C to obtain high-purity α-NaFeO2, which was denoted as orange-red powder C.

[0071] (3) Weigh 2.5g of orange-red powder C obtained in step (2) and 5.2g of N-MXene into an agate mortar and mix evenly. Then transfer it to a ball milling jar, add ball milling beads of different sizes into the jar, and ball mill at 430r / min for 7h. After milling, take it out to obtain solid powder D.

[0072] The solid powder D was placed in a quartz boat, and the quartz boat containing the sample was transferred to a tube furnace. Under an argon atmosphere, it was calcined at 500°C for 3.0 h. After the tube furnace was cooled to room temperature, the sample was removed, which is the α-NaFeO2@N-MXene composite material.

[0073] Example 3

[0074] An α-NaFeO2@N-MXene composite material and its preparation method are described below:

[0075] (1) Place 5.0g of NaOH and 8.0g of α-Fe2O3 in an agate mortar and mix evenly. Then transfer the mixture to a ball milling jar, add ball milling beads of different sizes into the jar, and mill at 500r / min for 5h. After milling, take it out to obtain reddish-brown solid powder A.

[0076] The reddish-brown solid powder A was placed in a corundum boat, and the corundum boat was transferred to a corundum tube furnace. It was calcined at 500°C for 3.5 hours in a N2 atmosphere. After cooling to room temperature with the furnace, α-NaFeO2 containing impurity phases was obtained, which was denoted as orange powder B (crude product).

[0077] (2) The orange powder B obtained in step (1) was washed and purified with ethylene glycol. Then the washed powder was dried in a vacuum drying oven at 60°C to obtain high-purity α-NaFeO2, which was denoted as orange-red powder C.

[0078] (3) Weigh 1.0g of the orange-red powder C obtained in step (2) and 3.5g of N-Mxene, place them in an agate mortar and mix them evenly. Then transfer them to a ball milling jar, add ball milling beads of different sizes into the jar, and ball mill at 400r / min for 12h. After that, take them out to obtain solid powder D.

[0079] The solid powder D was placed in a quartz boat, and the quartz boat containing the sample was transferred to a tube furnace. The sample was calcined at 400°C for 3.0 h under an argon atmosphere. After the tube furnace was cooled to room temperature, the sample was removed, which is the α-NaFeO2@N-MXene composite material.

[0080] Comparative Example 1

[0081] An α-NaFeO2@N-MXene composite material and its preparation method are described below:

[0082] (1) 4.24g of NaNO3 and 3.2g of Fe2O3 were placed in an agate mortar and mixed evenly, then transferred to a ball mill jar. Ball milling beads of different sizes were added to the jar, and the mixture was ball milled at 350r / min for 6h. The resulting brown solid powder A was obtained.

[0083] The brown solid powder A was placed in a corundum boat, and the corundum boat was transferred to a corundum tube furnace. Under N2 atmosphere, it was calcined at 600°C for 5 hours and then cooled to room temperature with the furnace to obtain α-NaFeO2 containing impurity phases, which was denoted as orange powder B (crude product).

[0084] (2) The orange powder B obtained in step (1) was washed and purified with anhydrous ethanol. Then the washed powder was dried in a vacuum drying oven at 100°C to obtain high-purity α-NaFeO2, which was denoted as orange-red powder C.

[0085] (3) Weigh 1.5g of the orange-red powder C obtained in step (2) and mix it with 3.5g of N-MXene in an agate mortar. Then transfer it to a ball milling jar, add ball milling beads of different sizes into the jar, and ball mill at 400r / min for 12h. After that, take it out to obtain solid powder D.

[0086] The solid powder D was poured into a quartz boat, and the quartz boat containing the sample was transferred to a tube furnace and calcined at 500°C for 2.5 hours in an oxygen atmosphere. After the tube furnace was cooled to room temperature, the sample was removed, which is the α-NaFeO2@N-MXene composite material.

[0087] Comparative Example 2

[0088] An α-NaFeO2@N-MXene composite material and its preparation method are described below:

[0089] (1) 4.24g of NaNO3 and 3.2g of Fe2O3 were placed in an agate mortar and mixed evenly, then transferred to a ball mill jar. Ball milling beads of different sizes were added to the jar, and the mixture was ball milled at 350r / min for 6 hours. The resulting brown solid powder A was obtained.

[0090] The brown solid powder A was poured into an alumina boat, and the alumina boat was transferred to an alumina tube furnace. Under N2 atmosphere, it was calcined at 600°C for 5 hours. After cooling to room temperature with the furnace, α-NaFeO2 containing impurity phase was obtained, which was denoted as orange powder B (crude product).

[0091] (2) The orange powder B obtained in step (1) was washed and purified with anhydrous ethanol. Then the washed powder was dried in a vacuum drying oven at 100°C to obtain high-purity α-NaFeO2, which was denoted as orange-red powder C.

[0092] (3) Weigh 1.5g of orange-red powder C obtained in step (2) and 0.75g of N-MXene into an agate mortar and mix evenly. Then transfer it to a ball milling jar, add ball milling beads of different sizes into the jar, and ball mill at 400r / min for 12h. After that, take it out to obtain solid powder D.

[0093] The solid powder D was poured into a quartz boat, and the quartz boat containing the sample was transferred to a tube furnace. Under an argon atmosphere, it was calcined at 500°C for 2.5 hours. After the tube furnace was cooled to room temperature, the sample was removed, which is the α-NaFeO2@N-MXene composite material.

[0094] Comparative Example 3

[0095] An α-NaFeO2@N-MXene composite material and its preparation method are described below:

[0096] (1) 4.24g of NaNO3 and 3.2g of Fe2O3 were placed in an agate mortar and mixed evenly, then transferred to a ball mill jar. Ball milling beads of different sizes were added to the jar, and the mixture was ball milled at 350r / min for 6 hours. The resulting brown solid powder A was obtained.

[0097] The brown solid powder A was poured into an alumina boat, and the alumina boat was transferred to an alumina tube furnace. Under N2 atmosphere, it was calcined at 600°C for 5 hours. After cooling to room temperature with the furnace, α-NaFeO2 containing impurity phase was obtained, which was denoted as orange powder B (crude product).

[0098] (2) The orange powder B obtained in step (1) was washed and purified with anhydrous ethanol. Then the washed powder was dried in a vacuum drying oven at 100°C to obtain high-purity α-NaFeO2, which was denoted as orange-red powder C.

[0099] (3) Weigh 0.5g of the orange-red powder C obtained in step (2) and 8g of N-MXene into an agate mortar and mix evenly. Then transfer it to a ball milling jar, add ball milling beads of different sizes into the jar, and ball mill at 400r / min for 12h. After milling, take it out to obtain solid powder D.

[0100] The solid powder D was poured into a quartz boat, and the quartz boat containing the sample was transferred to a tube furnace. Under an argon atmosphere, it was calcined at 500°C for 2.5 hours. After the tube furnace was cooled to room temperature, the sample was removed, which is the α-NaFeO2@N-MXene composite material.

[0101] Comparative Example 4

[0102] An α-NaFeO2@N-MXene composite material and its preparation method are described below:

[0103] (1) 4.24g of NaNO3 and 3.2g of Fe2O3 were placed in an agate mortar and mixed evenly, then transferred to a ball mill jar. Ball milling beads of different sizes were added to the jar, and the mixture was ball milled at 350r / min for 6h. The resulting brown solid powder A was obtained.

[0104] The brown solid powder A was placed in a corundum boat, and the corundum boat was transferred to a corundum tube furnace. Under N2 atmosphere, it was calcined at 600°C for 5 hours and then cooled to room temperature with the furnace to obtain α-NaFeO2 containing impurity phases, which was denoted as orange powder B (crude product).

[0105] (2) The orange powder B obtained in step (1) was washed and purified with anhydrous ethanol. Then the washed powder was dried in a vacuum drying oven at 100°C to obtain high-purity α-NaFeO2, which was denoted as orange-red powder C.

[0106] (3) Weigh 1.5g of the orange-red powder C obtained in step (2) and 3.5g of MXene (undoped N) into an agate mortar and mix evenly. Then transfer it to a ball milling jar, add ball milling beads of different sizes into the jar, and ball mill at 400r / min for 12h. After that, take it out to obtain solid powder D.

[0107] The solid powder D was placed in a quartz boat, and the quartz boat containing the sample was transferred to a tube furnace. Under an argon atmosphere, it was calcined at 500°C for 2.5 hours. After the tube furnace was cooled to room temperature, the sample was removed, which is the α-NaFeO2@N-MXene composite material.

[0108] Comparative Example 5

[0109] An α-NaFeO2@N-MXene composite material and its preparation method are described below:

[0110] (1) Place 5.0g of NaOH and 8.0g of α-Fe2O3 in an agate mortar and mix evenly. Then transfer the mixture to a ball milling jar, add ball milling beads of different sizes into the jar, and mill at 500r / min for 5h. After milling, take it out to obtain reddish-brown solid powder A.

[0111] The reddish-brown solid powder A was placed in a corundum boat, and the corundum boat was transferred to a corundum tube furnace. It was calcined at 520°C for 6 hours in a N2 atmosphere. After cooling to room temperature with the furnace, α-NaFeO2 containing impurity phases was obtained, which was denoted as orange powder B (crude product).

[0112] (2) The orange powder B obtained in step (1) was washed and purified with ethylene glycol. Then the washed powder was dried in a vacuum drying oven at 60°C to obtain high-purity α-NaFeO2, which was denoted as orange-red powder C.

[0113] (3) Weigh 1.0g of the orange-red powder C obtained in step (2) and 3.5g of N-Mxene, place them in an agate mortar and mix them evenly. Then transfer them to a ball milling jar, add ball milling beads of different sizes into the jar, and ball mill at 400r / min for 12h. After that, take it out to obtain the α-NaFeO2@N-MXene composite material.

[0114] Comparative Example 6

[0115] An α-NaFeO2 cathode material was prepared using the methods in steps (1) and (2) of Example 1.

[0116] The electrochemical performance of the α-NaFeO2@N-MXene composite materials provided in Examples 1-3 and Comparative Examples 1-6 was tested and compared with that of the α-NaFeO2 cathode material in Comparative Example 6. The specific methods are as follows:

[0117] Sodium-ion button batteries were assembled using the α-NaFeO2@N-MXene composite material (positive electrode material): The positive electrode material, conductive agent (conductive carbon black SP), and binder (polyvinylidene fluoride, PVDF) were mixed at a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) solvent was added to form a homogenate, resulting in a positive electrode slurry. This slurry was then coated onto aluminum foil and vacuum-dried at 90°C to prepare a positive electrode sheet. The prepared positive electrode sheet was used as the working electrode, metallic sodium as the counter electrode, and glass fiber cloth as the separator. NaFP6 electrolyte (a combination of ethylene carbonate EC and propylene carbonate PC solvent) from Tinci Materials Co., Ltd. was used. The button batteries were assembled in an argon-filled glove box. After assembly, the batteries were tested using a Blue Battery Testing System. For the performance testing, the current range for rate performance was set to 1C. Based on the rate performance test value of Comparative Example 6, the rate improvement rate of Examples 1-3 and Comparative Examples 1-5 was the rate of improvement of their respective rate performance test values ​​relative to the rate performance test value of Comparative Example 6, i.e., rate improvement rate = 100% × their respective test value / Comparative Example 6 test value - 100%. For cycle performance, the current density was 100mAh, the number of cycles was 80, and the voltage range was 2.0-3.4V. The cycle improvement rate was the specific capacity improvement rate after cycling, based on the specific capacity test value after cycling of Comparative Example 6. The cycle improvement rate of Examples 1-3 and Comparative Examples 1-5 was the rate of improvement of their respective specific capacity test values ​​after cycling relative to the specific capacity test value after cycling of Comparative Example 6. The test results are shown in Table 1.

[0118] Table 1

[0119]

[0120]

[0121] As can be seen from the performance data in Table 1, the preparation method provided by this invention, thanks to the introduction of N-MXene and its combination with specific processes, through the design and further optimization of materials and process routes in Examples 1-3, enables the prepared α-NaFeO2@N-MXene composite material to have excellent conductivity and stable two-dimensional ion conduction channels. This not only effectively improves the rate performance and cycle performance of the composite material, but also effectively suppresses the collapse of the layered structure of the α-NaFeO2 electrode material during the charging and discharging process, thereby reducing the rate of capacity decay and improving the initial coulombic efficiency. The initial coulombic efficiency is ≥87.5%, the cycle capacity retention rate is ≥92.3%, the rate improvement rate is ≥12.3%, the cycle improvement rate is ≥12.0%, and the electrochemical performance is significantly improved.

[0122] In the preparation method provided by this invention, α-NaFeO2 and N-MXene are mixed in a specific ratio and calcined in an inert atmosphere. This allows N-MXene to effectively coat and modify α-NaFeO2, constructing special conductive channels, thereby obtaining an α-NaFeO2@N-MXene composite material with excellent conductivity, rate performance, first coulombic efficiency, and cycle performance. Comparing Examples 1-3 with Comparative Example 1, it can be seen that if the mixture of α-NaFeO2 and N-MXene is calcined in oxygen, a stable α-NaFeO2@N-MXene composite material cannot be constructed due to the oxidation of N-MXene, resulting in significantly insufficient electrochemical performance. According to Examples 1 and Comparative Examples 2-3, if the mass ratio of α-NaFeO2 to N-MXene exceeds a specific range, the improvement effect of N-MXene on the electrochemical performance of α-NaFeO2 is poor. In Comparative Example 4, MXene was used for modification. However, due to the inferior conductivity and ductility of MXene compared to N-MXene, its synergistic effect with α-NaFeO2 was poor. Although it did improve the electrochemical performance of α-NaFeO2 to some extent, the overall performance was lower than that of Examples 1-3. In the composite material of Comparative Example 5, N-MXene and α-NaFeO2 were not calcined after mixing, making it difficult for N-MXene to adhere to α-NaFeO2 and form a continuous conductive network. This significantly reduced the improvement effect on the electrochemical performance of α-NaFeO2.

[0123] The applicant declares that this invention illustrates the α-NaFeO2@N-MXene composite material, its preparation method, and its application through the above embodiments. However, this invention is not limited to the above process steps, meaning that this invention does not necessarily rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to this invention, equivalent substitutions of the raw materials used in this invention, additions of auxiliary components, and selection of specific methods all fall within the protection and disclosure scope of this invention.

Claims

1. A method for preparing an α-NaFeO2@N-MXene composite material, characterized in that, The preparation method includes the following steps: The sodium source and the iron source were mixed and calcined once to obtain α-NaFeO2; The α-NaFeO2 and N-Mxene were mixed and then calcined twice to obtain the α-NaFeO2@N-MXene composite material; The mass ratio of α-NaFeO2 to N-Mxene is 1:(1-10), and the atmosphere for the secondary calcination is an inert atmosphere.

2. The preparation method according to claim 1, characterized in that, The method for mixing the sodium source and the iron source is ball milling.

3. The preparation method according to claim 2, characterized in that, The method for mixing the sodium source and the iron source is dry ball milling.

4. The preparation method according to claim 2, characterized in that, The ball milling mixing time is 0.5-12 h.

5. The preparation method according to claim 2, characterized in that, The ball milling speed is 200-500 r / min.

6. The preparation method according to claim 1, characterized in that, The molar ratio of sodium in the sodium source to iron in the iron source is 1:(0.1-10).

7. The preparation method according to claim 1, characterized in that, The temperature of the first calcination is 300-1000℃.

8. The preparation method according to claim 1, characterized in that, The calcination time for one calcination is 3-24 h.

9. The preparation method according to claim 1, characterized in that, The atmosphere for the first calcination includes any one or a combination of at least two of the following: air, oxygen, argon, and nitrogen.

10. The preparation method according to claim 1, characterized in that, The process after the first calcination also includes a purification step.

11. The preparation method according to claim 10, characterized in that, The purification method is washing and drying.

12. The preparation method according to claim 11, characterized in that, The washing reagent is an organic solvent.

13. The preparation method according to claim 11, characterized in that, The washing reagent is any one or a combination of two or more of ethanol, ethylene glycol, dimethyl carbonate, methanol, propanol, and butanol.

14. The preparation method according to claim 1, characterized in that, The purity of the α-NaFeO2 is above 98%.

15. The preparation method according to claim 1, characterized in that, The method for mixing α-NaFeO2 and N-Mxene is ball milling.

16. The preparation method according to claim 15, characterized in that, The method for mixing α-NaFeO2 and N-Mxene is dry ball milling.

17. The preparation method according to claim 15, characterized in that, The ball milling mixing time is 5-10 h.

18. The preparation method according to claim 15, characterized in that, The ball milling speed is 200-500 r / min.

19. The preparation method according to claim 1, characterized in that, The temperature of the secondary calcination is 200-500℃.

20. The preparation method according to claim 1, characterized in that, The secondary calcination time is 2-10 h.

21. The preparation method according to claim 1, characterized in that, The inert atmosphere for the secondary calcination is argon and / or nitrogen.

22. The preparation method according to claim 1, characterized in that, The sodium source includes any one or a combination of at least two of sodium oxide, sodium hydroxide, and sodium salt.

23. The preparation method according to claim 1, characterized in that, The sodium source includes any one or a combination of at least two of sodium carbonate, sodium nitrate, sodium acetate, sodium oxalate, sodium hydroxide, sodium sulfate, and sodium peroxide.

24. The preparation method according to claim 1, characterized in that, The iron source includes any one or a combination of at least two of ferric salts, ferrous salts, and iron oxides.

25. The preparation method according to claim 1, characterized in that, The iron source includes any one or a combination of at least two of the following: ferric nitrate, ferric oxide, ferrous oxalate, ferric oxide, ferrous sulfate, and ferric chloride.

26. The preparation method according to claim 1, characterized in that, The preparation method specifically includes the following steps: Sodium source and iron source were mixed by dry ball milling and then calcined at 300-1000℃ for 3-24 h to obtain crude product; The crude product was washed with an organic solvent and dried to obtain α-NaFeO2, and the purity of the α-NaFeO2 was above 98%. The α-NaFeO2 and N-MXene were dry ball-milled at a mass ratio of 1:(1-10) and then calcined at 200-500℃ in an inert atmosphere for 2-10 h to obtain the α-NaFeO2@N-MXene composite material.

27. An α-NaFeO2@N-MXene composite material, characterized in that, The α-NaFeO2@N-MXene composite material was prepared using the preparation method described in any one of claims 1-26.

28. A sodium-ion battery, characterized in that, The sodium-ion battery includes the α-NaFeO2@N-MXene composite material as described in claim 27.

Citation Information

Patent Citations

  • O3 / p2 mixed phase sodium-containing doped layered oxide materials

    CN112262109A

  • Iron-based layered oxide positive electrode active material and preparation method and application thereof

    CN113716622A

  • Composite nano material for sodium ion battery and preparation method of composite nano material

    CN114220961A

  • MXene composite modified binary manganese-based sodium electric precursor and preparation method thereof

    CN114604896A